Med-arb and arb-med procedures in conflicts among professionals in agriculture - Ioan Niculae Alecu; Felix-Dimitrie Ciocan; Horia Nicolae Ciocan; Miki Mihuţ (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 6th Edition of the International Symposium, November 2015, Bucharest, 2015)
Disputes among professionals in agronomy are generally caused by failure in performing a contract, most often the result of unclear formulations or of some flaws in drafting a contract. These arise from a failure to observe objective law, the non-satisfaction of subjective law and a failure to perform one's obligations. These are moments when Med-Arb is needed to resolve disputes and preserve business relationships between farmers. First, we must emphasize that the ADR (Alternative Dispute Resolution) phenomenon is far smaller in Romania when compared to the United States of America (a leader in the field, as previously shown), but also as to any other West European country that holds a tradition in the field. The ratio between classical state justice and alternate methods for dispute resolution is overwhelmingly in favour of the former. Thus, from data provided by the Superior Council of Magistracy, in 2014, at a national level, there were over 4,200,000 cases on the docket before courts of law and only 800-900 cases before The Romanian Court of International Commercial Arbitration. As regards mediation, The Mediation Council declared several thousand mediations carried over 2014. The purpose of this paper is to carry out an analysis on out-of-court alternatives for dispute resolution in business relationships among agribusiness professionals or between agribusiness professionals ans professionals from other fields, with whom they establish varied legal relationships.
Keywords: 330; mediation; arbitration; agronomy; Med-Arb; dispute